Association of the Helicobacter pylori cagA, vacA, and iceA genotypes with chronic follicular gastritis in a Colombian population at high risk for gastric cancer (2019)
Introduction and objective Follicular gastritis is associated with Helicobacter pylori infection, but little is known of its relation to bacterial genotypes. Our aim was to establish the relation between follicular gastritis and different H. pylori strains. Materials and methods An analytic case-control study was conducted that included 36 patients with follicular gastritis (cases) and 83 with nonatrophic gastritis (controls). The sociodemographic information was obtained through a questionnaire. Biopsies were evaluated according to the Sydney System and the Wotherspoon scoring system. Helicobacter pylori genotyping was performed using the polymerase chain reaction technique. The quantitative variables were presented as mean and standard deviation and the qualitative variables as proportions and absolute frequency. The effect of each variable on outcome (follicular gastritis) was evaluated through the odds ratio and its 95% confidence interval. Statistical significance was set at a p < 0.05. Results Follicular gastritis was associated with Helicobacter pylori infection (OR: 13.41, CI: 1.7-103, p = 0.01). The CagA+ genotype was present in 56.5% of the cases and 58% of the controls. The cytotoxic VacAs1m1strain was present in 82% of the isolates in both groups. IceA1 frequency was 34.8% in the cases and 26% in the controls and the difference was not statistically significant. Conclusions The population studied had elevated frequencies of cytotoxic Helicobacter pylori strains and the iceA1 genotype was more frequent in follicular gastritis.